Intraoperative Photodiagnosis for Malignant Glioma Using Photosensitizer Talaporfin Sodium - Akimoto, Jiro; Fukami, Shinjiro; Ichikawa, Megumi; Mohamed, Awad; Kohno, Michihiro (Frontiers in Surgery, 2019)
Objective: The aim of this study was to demonstrate the clinical feasibility of intraoperative photodiagnosis (PD) of malignant brain tumor using talaporfin sodium (TPS), which is an agent used in photodynamic therapy (PDT) for cancers. Methods: Forty-seven patients diagnosed with malignant gliomas by preoperative imaging (42 patients with gliomas and 5 patients with other brain tumors) received an intravenous injection of TPS at 40 mg/m2 24 hours before resection. During surgery, these patients were irradiated with diode laser light at 664 nm, and tumor fluorescence was observed. The fluorescence intensity was visually rated on a 3-point rating scale [strong fluorescence, weak fluorescence and no fluorescence]. TPS concentrations in 124 samples from 47 cases were measured by HPLC (High performance liquid chromatography). Results: The fluorescence intensity was confirmed to be weak in all patients with Grade II gliomas and strong in almost all patients with Grade III or IV gliomas, reflecting the histological grade of malignancy. In patients with non-glioma brain tumors except for 1 patient with a metastatic brain tumor, the fluorescence intensity was strong. The mean TPS concentration in tissues was 1.62 μg/g for strong fluorescence areas, 0.67 g/g for weak fluorescence areas and 0.19 μg/g for no fluorescence areas. Conclusions: Establishment of an appropriate fluorescence observation system enabled fluorescence-guided resection of malignant brain tumors using TPS, and the fluorescence intensity of tumors correlated with the TPS concentrations in tissues. These results suggest that TPS is a useful photosensitizer for both intraoperative fluorescence diagnosis and photodynamic therapy.